Recommendations given not to victimise any quarters — A-G - Borneo Post, (Kuching) (Borneo Post, 2017)
Shah Alam: The recommendations given in the Auditor-General's Report are not aimed at victimising or discrediting any organisation or its staff but instead to help make improvements, said Auditor- General Tan Sri Dr Madinah Mohamad.